Enhanced microalgae harvesting in a microfluidic centrifugal separator. (April 2022) - Sharma, Rohan; Kim, Myeongsub
Abstract: Biofuel is a promising renewable energy source that has gained interest in recent years due to its viability and sustainability. Microalgae in particular have three orders of magnitude higher in oil-to-fuel yield when compared with other crop-based feedstocks, and therefore microalgal biofuels have the substantial potential to meet national energy demands. One challenge of the microalgae-derived biofuels is limited harvesting efficiency, prompting an urgent need for alternative harvesting methods that are cost-effective and viable. Centrifugation has been used as one such method of separation due to its simple principle and effectiveness. However, most centrifugation methods lie in the high operating costs as opposed to other mechanical or chemical methods. To maximize separation efficiency while also limiting costs, we hereby demonstrate a spiral microalgae separator consistent with the centrifugal method, along with manipulating selected parameters of the algal medium to achieve a degree of separation within a single experiment that yields significantly more concentrated algal slurry. Concentration, temperature, and pH manipulation were among the few selected parameters that we found to yield high concentrations within single, rapid separations in seconds. Initial concentration of algae solutions was found to relate proportionally to separation efficiency. Algae solutions at lower density experienced flocculation that aids in the separation and centrifugal effect whereas high density samples experienced flocculation of algal groups too large for efficient separation. Similarly, basic pH and higher temperature manipulations specifically targeted the flocculation of microalgae particles to form larger groups, with more efficient harvesting. These parameters enable the principle and benefits of microfluidic centrifugal separation to be demonstrated on the microalgae flow, with the ability to be scaled up using parallelization of multiple platforms: a viable alternative to the conventional centrifugal method. Highlights: A microfluidic centrifugal platform provides the highest separation efficiency of microalgae. Initial algae concentration is a critical factor in achieving high separation efficiency. Basic pH helps algae aggregate leading to high separation efficiency. The temperature effect on algae separation is concentration-dependent.